The Perceptions of the Use E-Journal by English Department Students at Fatmawati Sukarno State Islamic University Bengkulu in Fulfilling the Needs for Academic Writing During Pandemic - Chindy Yulia Permatasari; Ali Akbarjono; Feny Martina (JPT : Jurnal Pendidikan Tematik, 2022)
This research aimed to determine the perception and use of E-Journals in fulfilling academic writing needs by 8th-semester students of the English Department at UIN Fatmawati Sukarno Bengkulu during the COVID pandemic. Thus the variable consists of two, namely the dependent variable Academic Writing with the following indicators are Using resources to achieve academic writing, Level of staff in finding sources, Frequency of accessing sources, Scope of source search, and Determining the required information sources. While the independent variables consist of E-Journal-free indicators are Utilization, Update, Accessibility, Frequency, Speed, Convenience, and Security. This research method uses quantitative descriptive with samples taken using a random sampling technique consisting of a sample of 60 students. Then for data collection has used the instrument through questionnaires and observations. This research's results indicate that the study Level of student e-journal perceptions during the pandemic was on a scale of 3.31 (good). Furthermore, the study results showed that the level of use of e-journals as a source of information for academic writing is on a scale of 3.16 (good). In this case, the researcher suggests several things that need to be improved, including increasing the means of accessing e-journals and improving in updating and completeness of e-journal websites.